ANALISIS KESADARAN MEREK DAN PERSEPSI RISIKO TERHADAP NIAT BELI PRODUK PAKAIAN DI ONLINE SHOPEE STUDI KASUS KARYAWAN PT. ENIGMA HASBUNA INDONESIA - Saifullah Saifullah; Rudianto Hermawan; Muhamad Roby Jatmiko; Yuliantin Yuliantin; Endro Susilo (LPSDI Bina Patria, 2023)
The purpose of this study was to analyze the brand awareness and effect of risk perception on fashion product purchase intention at Shopee for the Employees PT. Eniqma Hasbuna Indonesia. The approach in this study was a quantitative approach. The data collection technique was based on questionnaires and literature studies. The population used in this study were Employees s of the PT. Eniqma Hasbuna Indonesia. The sampling technique was the random sampling method. The sample in this study was 54 respondents. The data analysis technique used was SPPSS version 25 software. Based on the results of data analysis of multiple linear equations, it was found that risk perception and brand awareness have a simultaneous positive effect on purchase intention. From the results of the partial test analysis, risk perception has a positive effect on purchase intention and brand awareness also has a positive effect on purchase intention. It is proven by the results of the calculation of the coefficient of determination (R2) that there is a significant and positive effect between brand awareness (X1) and risk perception (X2) on purchase intention (Y) by 0.595 or 59.5% while the remaining 40.5% is determined by other variables not included in this study